2000
DOI: 10.1177/135245850000600406
|View full text |Cite
|
Sign up to set email alerts
|

Visuoperceptual impairment in multiple sclerosis patients diagnosed with neuropsychological tasks

Abstract: A comprehensive set of 31 binocular neuropsychological tasks assessing a series of spatial and non-spatial visuoperceptual abilities was used to study visuoperceptual impairment in a representative group of 49 MS-clinic patients exhibiting neither diagnosed ophthalmological afflictions nor major psychiatric diagnoses. Among these patients, true frequency rate of visuoperceptual impairment, i.e. of subjects failing four or more tasks, was estimated at 26%. The pattern of visuoperceptual impairment was non-unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 57 publications
(74 reference statements)
1
23
0
5
Order By: Relevance
“…33,43 The results are also consistent with prior studies showing that subjects with MS perform significantly worse than HCs on cognitive tests assessing processing speed, working and visual-spatial processing/memory, sustained attention, and executive function. 21,[44][45][46] The diffuse SLE syndromes such as anxiety disorders, mood disorders, headache, and cognitive impairment may be the result of diffuse damage, whereas focal SLE syndromes such as seizures, strokes, and transient ischemic attacks, result in high-attenuation focal lesions. Several studies have shown regionally-specific decreased FA and increased MD in patients with NPSLE compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…33,43 The results are also consistent with prior studies showing that subjects with MS perform significantly worse than HCs on cognitive tests assessing processing speed, working and visual-spatial processing/memory, sustained attention, and executive function. 21,[44][45][46] The diffuse SLE syndromes such as anxiety disorders, mood disorders, headache, and cognitive impairment may be the result of diffuse damage, whereas focal SLE syndromes such as seizures, strokes, and transient ischemic attacks, result in high-attenuation focal lesions. Several studies have shown regionally-specific decreased FA and increased MD in patients with NPSLE compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of impaired cognitive performance in MS has been replicated many times (Beatty et al 1989;Fischer 1988;Rao et al 1993). Other cognitive impairments have been described, involving such domains as spatial processing (Vleugels et al 2000), verbal fluency (Beatty 2002), and higher executive function (Arnett et al 1997;Beatty et al 1995;Beatty and Monson 1996;Foong et al 1997). Neuropsychological defects are associated with progressive more than relapsing disease course (Beatty et al 1988) and MRI evidence of lesion burden and brain atrophy (Amato et al 2004;Benedict et al 2002aBenedict et al , 2004aChristodoulou et al 2003;Rao et al 1989a).…”
Section: Comparison With Msmentioning
confidence: 99%
“…The neurological disorders investigated in the present report (i.e., multiple sclerosis [MS] and Duchenne muscular dystrophy [DMD]) are known to affect neuropsychological function (Balsimelli, Mendes, Bertolucci, & Tilbery, 2007;Beatty, Goodkin, Monson, & Beatty, 1989;Cyrulnik et al, 2008;D'Angelo & Bresolin, 2006;De Luca, Chelune, Tulsky, Lengenfelder, & Chiaravalloti, 2004;Desguerre et al, 2009;Dorman, Hurley, & D'Avignon, 1988;Giliberto, Ferreiro, Dalamon, & Szijan, 2004;Grant, McDonald, Trimble, Smith, & Reed, 1984;Hinton, De Vivo, Nereo, Goldstein, & Stern, 2001;Laatu, Revonsuo, Hämäläinen, Ojanen, & Ruutiainen, 2001;Miller, Tunnecliffe, & Douglas, 1985;Moizard et al, 1998;Parmenter, Schucerd, Benedict, & Schucard, 2006;Parmenter, Shucard, & Shucard, 2007;Plohmann et al, 1998;;Rao, 2004;Ruggieri et al, 2003;Santiago, Guardia, Casado, Carmona, & Arbizu, 2007;Vleugels et al, 2000Vleugels et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%